Therapeutic strategies of iron-based nanomaterials for cancer therapy. (3rd March 2021) - Wu, Xiaqing; Zhang, Haiyuan
Abstract: Iron-based nanomaterials have appeared in various cancer treatments owing to their promising functions and safety. Various sophisticated iron-based nanomaterials have been designed to exhibit great therapeutic effects through different strategies. Given the rapid progression, there is a great need to integrate the recent advances to learn about the latest innovation in this field. In this review, we classified the strategies of iron-based nanomaterials for cancer treatment into the following categories: immunotherapy, ferroptosis, magnetic hyperthermia and magneto-mechanical destruction. On the one hand, we discussed the underlining mechanism of iron-based nanomaterials in these therapies and applications; on the other hand, we analyzed the feasible combination of these applications and other therapies. Finally, the current challenges and expectation of iron-based nanomaterials in this field were highlighted.